Le Revisioni Narrative nella ricerca degli studenti di infermieristica italiani: tra aspirazione e rigore - Mauro Parozzi; Paolo Ferrara; Anne Destrebecq; Stefano Terzoni (Dissertation Nursing, 2025)
In the context of Italian nursing education, narrative literature reviews have long been a commonly adopted starting point across the country. However, their methodologically flexible nature often makes them a slippery ground for research novices. This editorial critically examines a sample of thirty narrative reviews submitted to Dissertation Nursing between 2022 and 2024, highlighting methodological, stylistic, and content-related limitations. Common practices emerge, such as the confused hybridization with systematic reviews, the inappropriate use of structured tools without proper justification, and a lack of critical reflection. Added to this are unsuitable writing styles and a general excess of description at the expense of scientific meaning-making. The article questions the educational effectiveness of narrative reviews as an initial approach to research and proposes a pedagogical and operational rethinking to enhance the value of this tool, preventing it from becoming a mere academic exercise devoid of genuine scientific impact.